2015
DOI: 10.1242/bio.010447
|View full text |Cite
|
Sign up to set email alerts
|

Zebrafish adult-derived hypothalamic neurospheres generate gonadotropin-releasing hormone (GnRH) neurons

Abstract: Gonadotropin-releasing hormone (GnRH) is a hypothalamic decapeptide essential for fertility in vertebrates. Human male patients lacking GnRH and treated with hormone therapy can remain fertile after cessation of treatment suggesting that new GnRH neurons can be generated during adult life. We used zebrafish to investigate the neurogenic potential of the adult hypothalamus. Previously we have characterized the development of GnRH cells in the zebrafish linking genetic pathways to the differentiation of neuromod… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
9
0
1

Year Published

2015
2015
2021
2021

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 13 publications
(13 citation statements)
references
References 64 publications
(86 reference statements)
3
9
0
1
Order By: Relevance
“…In teleosts, GnRH1 peptide is having hypophysiotropic nature, as shown by the axonal projections of GnRH secreting neurons of POA into the pituitary gland through hypothalamo-hypophysial tract (Karigo & Oka, 2013). Moreover, the antibody employed in the present study was shown to label hypothalamic GnRH neurons of preoptic region in the zebrafish D. rerio (Cortes-Campos, Letelier, Ceriani, & Whitlock, 2015). Therefore, the GnRH immunoreactivity observed in the pituitary gland suggests that the antibody employed in the present study labeled GnRH1 neurons in G. affinis.…”
Section: Discussionsupporting
confidence: 55%
“…In teleosts, GnRH1 peptide is having hypophysiotropic nature, as shown by the axonal projections of GnRH secreting neurons of POA into the pituitary gland through hypothalamo-hypophysial tract (Karigo & Oka, 2013). Moreover, the antibody employed in the present study was shown to label hypothalamic GnRH neurons of preoptic region in the zebrafish D. rerio (Cortes-Campos, Letelier, Ceriani, & Whitlock, 2015). Therefore, the GnRH immunoreactivity observed in the pituitary gland suggests that the antibody employed in the present study labeled GnRH1 neurons in G. affinis.…”
Section: Discussionsupporting
confidence: 55%
“…For spheres in all the three groups, we observed that most cells in the spheres expressed Nestin and only a few sphere cells expressed GFAP (Figure S1B). The characteristics of these spheres correspond with that of neurospheres described in the literature …”
Section: Resultssupporting
confidence: 79%
“…The characteristics of these spheres correspond with that of neurospheres described in the literature. [48][49][50][51][52][53]…”
Section: Ep 4 Antagonist-induced Msc Evs/exosomes Promote the Formamentioning
confidence: 99%
“…Cortés-Campos et al . 43 demonstrated that adult zebrafish-derived hypothalamic neurospheres generate GnRH neurons, including GnRH3 ones. They also demonstrated that the number of GnRH neurons increased following exposure to testosterone or GnRH3.…”
Section: Discussionmentioning
confidence: 99%